Compatibility and Difference in News Coverage of the Russian-Ukrainian Conflict: An Analytical Study of the Main News Bulletins on Russia Today and Al-Hurra American Channels from 22-2 to 22-3 2022 - Hussein, Walaa Muhammad Ali (ALBAHITH ALALAMI, 2024)
This study compares the news coverage of the Russian-Ukrainian conflict on the Russian channel "Russia Today" and the American channel "Al-Hurra," highlighting the impact of political and ideological orientations on event reporting. The relationships and interests linking Russia and the United States to the conflict played a significant role in shaping the media coverage, resulting in differences in how news was presented and the terms used, reflecting divergent perspectives. The study employed content analysis of the main news bulletins over one month, starting from the onset of the Russian military operations in Ukraine, focusing on areas of agreement and disagreement between the two channels. The findings reveal: Russia Today used terms like "special operations" and "operations in Donbas," whereas Al-Hurra described these actions as illegitimate and referred to pro-Russian forces in Donbas as "separatists". Russia Today heavily emphasized justifying the war based on statements from Russian politicians, while Al-Hurra approached these justifications cautiously, casting doubt on their validity. This analysis illustrates how media coverage differs according to the political and ideological frameworks of each channel.